Literature Science Analysis on the Validity and Practicality Criteria of GeoGebra-Supported Mathematics Learning Modules - Nelvy Yunita; Suherman; Edwin Musdi; Zusti Jamaan (Postgraduate, University of Mataram, 2025)
This study presents a systematic literature review analyzing the validity and practicality of GeoGebra-supported mathematics learning modules. The purpose is to evaluate the scientific quality and classroom feasibility of these modules based on empirical evidence from published research between 2013 and 2023. A total of 27 studies were synthesized using PRISMA guidelines to assess content, construct, and instructional design validity, as well as ease of use, time efficiency, and user response. Findings indicate that most modules demonstrate high content validity through expert validation and curriculum alignment, and are perceived as practical and engaging by teachers and students. However, gaps exist in empirical validation of learning constructs and in the integration of cognitive load principles within instructional design. Challenges such as extended implementation time, technical barriers, and insufficient teacher training affect practicality in real classroom settings. The study concludes that while GeoGebra-supported modules hold strong potential for enhancing mathematics learning, their effectiveness depends on pedagogical soundness, systematic development, and contextual support. Standardized evaluation frameworks and improved teacher readiness are recommended for sustainable implementation.